Gothic Kernow : Cornwall as strange fiction - Krzywinska, Tanya; Heholt, Ruth (Anthem Press, 2022)
This book is focused on written and visual culture that is made in, or made about, Cornwall and where there is affinity with Gothic. Cornwall and the Scilly Isles (known as 'Kernow' in the Cornish language) have a special relationship with Gothic, one that has been overlooked in the literature on regional Gothic. In 1998, Avril Horner and Sue Zlosnik coined the term 'Cornish Gothic' in relation to the work of Daphne du Maurier. Since then, however, there have been few discussions of the distinctive types of Gothic engendered by cultural and imaginative re-creations of Cornwall or where it has played a generative role within creative practice. The book argues that a persistent imaginative romance with the peninsular has produced a specific and distinctive set of Gothic fictions and creative outputs that mark an exciting new departure in the discussion of regional and media-aware Gothic studies. Offering new insights into the relationships between place and Gothic, this book aims to engender and encourage greater debate through our argument that Cornwall plays a potent role in the landscape of regional Gothic and argues that it needs to be considered more fully as a major catalyst in the Gothic imagination.